PEMANFAATAN TEKNOLOGI REVOLUSI INDUSTRI 4.0 UNTUK LAPORAN KEUANGAN SEDERHANA WARUNG KOPI HJ JUNEN - Dewanahalim, Muhammad Arya; Virel, Oryza Sativa; Ajitama, Syandy Pramudya; Rivai, Ibnu; Rahmadi , Zara Tania (ASOSIASI IDEBAHASA KEPRI, 2025)
The Industrial Revolution 4.0 presents opportunities and challenges in managing MSME finances, especially due to limited digital literacy and resources. This research accompanies Warung Kopi Haji Junen through training and application of digital financial technology, such as QRIS and Microsoft Excel, to increase the efficiency of financial recording. The results show that the coffee shop has succeeded in preparing structured financial reports, including balance sheets, profit and loss and cash flow, although challenges in using technology are still encountered. This assistance proves the importance of digital technology in managing MSME finances and can be a reference for similar assistance in the future.